Global and regional patterns in cardiovascular mortality from 1990 to 2013 - Roth, Gregory A; Huffman, Mark D; Moran, Andrew E; Feigin, Valery; Mensah, George A; Naghavi, Mohsen; Murray, Christopher J L (Circulation (New York, N.Y.), 2015)
There is a global commitment to reduce premature cardiovascular diseases (CVDs) 25% by 2025. CVD mortality rates have declined dramatically over the past 2 decades, yet the number of life years lost to premature CVD deaths is increasing in low- and middle-income regions. Ischemic heart disease and stroke remain the leading causes of premature death in the world; however, there is wide regional variation in these patterns. Some regions, led by Central Asia, face particularly high rates of premature death from ischemic heart disease. Sub-Saharan Africa and Asia suffer disproportionately from death from stroke. The purpose of the present report is to (1) describe global trends and regional variation in premature mortality attributable to CVD, (2) review past and current approaches to the measurement of these trends, and (3) describe the limitations of existing models of epidemiological transitions for explaining the observed distribution and trends of CVD mortality. We describe extensive variation both between and within regions even while CVD remains a dominant cause of death. Policies and health interventions will need to be tailored and scaled for a broad range of local conditions to achieve global goals for the improvement of cardiovascular health.